Comparising DNA extraction from environmental DNA samples to reveal the diversity of freshwater metazoans - Donan Satria Yudha; Dwi Sendi Priyono; Rahma Izzati; Aulia Sigit Ardianto; Ananto Puradi; Nainggolan Nainggolan (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Environmental DNA (eDNA) monitoring has gained popularity in the last decade as one of the most sensitive and cost-effective monitoring methods. However, information regarding the type of DNA extraction used still needs to be studied, especially for metazoan in fresh water samples. This parameter is also critical for a project's experimental design. This study aims to compare the effectiveness of two extraction kits between DNeasy® Blood & Tissue Kit (Qiagen) silica column-based and ZymoBIOMICS 96 MagBead DNA Kit (Zymo Research) magnetic bead-based. The quantity of DNA extracts was measured using a spectrophotometer at 260/280 nm. Following that, we continued the metazoa PCR procedure. Qiagen has higher mean value of DNA concentration (88.48 ng/μl) than Zymo (20.89 ng/μl). For DNA purity, Zymo has higher mean value of DNA purity (1.84) than the Qiagen (1.59). However, both kits were equally successful in amplifying universal metazoan primers. We recommend that the use of these types of kits appears to be the least important consideration. Other important factors that may have a major impact on DNA extraction such as water volume, membrane type, sampling strategy need to be investigated in freshwater samples.